HUBUNGAN BUDAYA ORGANISASI DENGAN KOMITMEN ORGANISASI PADA PT. BANK TABUNGAN NEGARA (Persero), Tbk KANTOR CABANG PEKANBARU - Syawfitri Dewi; Lena Farida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Organizational culture is a belief and values that become the main philosophy adhered to by members of the organization to make the employees loyal and willing to work in a run or operational activities of the organization. Organizational commitment is an attitude that reflects the extent to which an individual knows and bound to the organization. An individual who has a strong commitment is likely to see himself as a true member of the organization. The purpose of this study is to understand the organizational culture, organizational commitment and examine the relationship of organizational culture and organizational commitment at The Branch Office PT. Bank Tabungan Negara (Persero),Tbk Pekanbaru The method used in this research is descriptive and analytical techniques used are quantitative analysis. The sampling technique used is the census method with a population equal to the number of respondents that amounted to 68 respondents. The data measured with Likert scale. And then the data is processes by using Spearman Rank Correlation formula.The results of this study indicate that the relationship of organizational culture on organizational commitment at The Branch Office PT. Bank Tabungan Negara (Persero), Tbk Pekanbaru showed relationship quite well or quite fix.Keyword : Organizational Culture, Organizational Commitment, The Branch Office PT. Bank Tabungan Negara (Persero), Tbk Pekanbaru